2023
DOI: 10.1037/tra0001264
|View full text |Cite
|
Sign up to set email alerts
|

Family involvement and secondary traumatization in Holocaust survivor families: An actor–partner interdependence model.

Abstract: Objective: The study aimed to examine the interpersonal relationships between family involvement (i.e., emotional and behavioral strategies that underscore family members’ well-being and familial legacy) and secondary traumatization (i.e., symptoms of distress resulting from close contact with a traumatized individual) in Holocaust survivors and comparison families. We assessed levels of family involvement and secondary traumatization in children and grandchildren of survivors (Holocaust G2 and G3) and compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…G2 and G3 did not have familial relationship to each other. As conducted in previous studies (e.g., Greenblatt-Kimron et al, 2021, 2023, G2 and G3 were born after World War II (after 1945). Holocaust G2 were children of parents who were both born before 1946, with at least one parent who lived in countries dominated by the Nazi or pro-Nazi regime during 1939-1945.…”
Section: Methods Participants and Proceduresmentioning
confidence: 69%
See 3 more Smart Citations
“…G2 and G3 did not have familial relationship to each other. As conducted in previous studies (e.g., Greenblatt-Kimron et al, 2021, 2023, G2 and G3 were born after World War II (after 1945). Holocaust G2 were children of parents who were both born before 1946, with at least one parent who lived in countries dominated by the Nazi or pro-Nazi regime during 1939-1945.…”
Section: Methods Participants and Proceduresmentioning
confidence: 69%
“…It is presumed that Holocaust survivor families are more susceptible to the intra-and interpersonal characteristics of trauma transmission (Shmotkin et al, 2011). From this perspective, Figure 1 Russo-Ukrainian War Salience in Holocaust and Comparison Families previous studies showed higher awareness of the family atmosphere in Holocaust families (Greenblatt- Kimron et al, 2023;Palgi et al, 2015), higher levels of family involvement (Greenblatt- Kimron et al, 2023), and higher levels of secondary traumatization (Giladi & Bell, 2013;Greenblatt-Kimron et al, 2021, 2023. Furthermore, dyadic analyses showed a link between greater family involvement and higher secondary traumatization in both Holocaust G2 and G3 and comparison G2 and G3; nevertheless, only in Holocaust G2 and G3 greater family involvement in one generation was related to higher secondary traumatization in the other generation.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations